Professional driving and prolapsed lumbar intervertebral disc diagnosed by magnetic resonance imaging: a case-control study - Keith T Palmer; Michael Griffin; Georgia Ntani; James Shambrook; Philip McNee; Madeleine Sampson; E Clare Harris; David Coggon (Nordic Association of Occupational Safety and Health (NOROSH), 2012)
OBJECTIVES: The aim of this study was to investigate whether whole-body vibration (WBV) is associated with prolapsed lumbar intervertebral disc (PID) and nerve root entrapment among patients with low-back pain (LBP) undergoing magnetic resonance imaging (MRI). METHODS: A consecutive series of patients referred for lumbar MRI because of LBP were compared with controls X-rayed for other reasons. Subjects were questioned about occupational activities loading the spine, psychosocial factors, driving, personal characteristics, mental health, and certain beliefs about LBP. Exposure to WBV was assessed by six measures, including weekly duration of professional driving, hours driven at a spell, and current 8-hour daily equivalent root-mean-square acceleration A(8). Cases were sub-classified according to whether or not PID/nerve root entrapment was present. Associations with WBV were examined separately for cases with and without these MRI findings, with adjustment for age, sex, and other potential confounders. RESULTS: Altogether 237 cases and 820 controls were studied, including 183 professional drivers and 176 cases with PID and/or nerve root entrapment. Risks associated with WBV tended to be lower for LBP with PID/nerve root entrapment but somewhat higher for risks of LBP without these abnormalities. However, associations with the six metrics of exposure were all weak and not statistically significant. Neither exposure-response relationships nor increased risk of PID/nerve root entrapment from professional driving or exposure at an A(8) above the European Union daily exposure action level were found. CONCLUSIONS: WBV may be a cause of LBP but it was not associated with PID or nerve root entrapment in this study.